Laparoscopic management for a psoas abscess caused by migrated urolithiasis. Issue 5 (22nd July 2019) - Kaneko, Go; Katsui, Masahiro; Hattori, Seiya; Hara, Satoshi
Abstract : Introduction: To describe laparoscopic surgery for psoas abscess caused by migrated urolithiasis. Case presentation: A 64‐year‐old female had renal stones in the right kidney for 5 years. She developed right back pain. Her body temperature was 37.4°C, and right costovertebral angle tenderness was detected. In blood examination, her C‐reactive protein level was elevated. Computed tomography revealed that one stone had migrated into the right psoas muscle and caused psoas abscess. Another stone was detected in the renal parenchyma. Percutaneous drainage and antibiotic treatment were performed until her symptoms and inflammation improved. However, psoas abscess recurred after removal of the drainage tube. The migrated stone was laparoscopically removed after fenestration of psoas abscess, and laparoscopic nephrolithotomy was simultaneously performed for the other stone. Conclusion: To the best of our knowledge, this is the first case report of psoas abscess caused by migrated urolithiasis that was managed by minimally invasive surgery.